Bioarte Brasileira e Vida Artificial: Investigação Teórica e Prática Artística - NOMURA, Luciana Hidemi Santana (2011)
This paper focuses on Brazilian production of one the currents of technology and arte, called bioart, with emphasis on one of its aspects called "artificial life art" - inspired by the dynamic processes of biological systems - which promote the emergency of digital artificial systems, dynamic and self-sustaining, named "artificial life". This reserach presentes featured works of Brazilian production of this emerging artistic category and analyses the poetic propositions of the artistis with emphasis on verifying the forms of interactivity of these works. Simultaneously with the exploraty investigation of the art in Brazil, it has been developed a project on "bioart" in which its goal is to explore some interactive possibilities of a system based on evolutionary algorithm and artificial life.